The Utilization of Artificial Intelligence in Enhancing Students' Character and Soft Skills in the Digital Era: A Literature Review - Fauziah, Fauziah (Lembaga Publikasi Ilmiah Dwipantara, 2025)
The advancement of digital technology has had a significant impact across various sectors, including education. One of the technologies that has been increasingly utilized is Artificial Intelligence (AI), which offers tremendous potential for enhancing students' character and soft skills. Although AI is widely used to support the development of technical skills, research on its application for enhancing students' soft skills remains limited. This article aims to explore the use of AI in improving students' character and soft skills in the digital age. The study employs a literature review approach, gathering and analyzing various relevant sources on AI and character education. Data were collected through a literature search of academic articles published between 2020 and 2025. The analysis was conducted by assessing the types of AI technologies utilized, the learning models integrated, and the impacts and challenges of implementing these technologies in education. The main findings indicate that technologies such as chatbots and AI-based adaptive learning systems have the potential to enhance students' communication, leadership, and empathy skills. However, challenges related to technology access and the objective measurement of character remain significant barriers. This research contributes to the development of technology-based education by offering insights into how AI can be applied to support the development of students' soft skills. In conclusion, while AI demonstrates great potential, further research is needed to address implementation challenges and to develop more effective AI-based evaluation tools.